Pengujian putusan kode etik penyelenggara pemilu dalam ranah Hukum Administrasi Negara - Damanik, Agussyah Ramadani (Jurnal Normatif, 2024)
The Elections is carried out based on the standard provisions of the Law and the Code of Ethics for the Implementation of Elections. According to the Indonesian electoral Law Number 7 of 2017 concerning Elections, the elements of the Election Organizer consist of the General Election Commission, the Election Supervisory Body and the Election Organizer Honorary Council which are a unified function of organizing elections. The role of the Election Organizer is highly demanded for its ability to implement the regulations of the election stages by heeding the Election Organizer Code of. The integrity and quality of the election are determined by the compliance of the election organizers in fulfilling the principles and ethics of election organizers as the basic formula for the formulation of the Election Organizer Code of Ethics, so that the enforcement of the Election Organizer Code of Ethics (rule of ethics) is a necessity in our democratic system. DKPP is authorized by law to carry out the function of maintaining the integrity, independence and credibility of the Election Organizer. DKPP can impose ethical sanctions on election organizers from warning sanctions to permanent dismissal of election organizers with the power of its decision instrument which was originally final and binding (Article 458 paragraph 3 of the Election Law). The provision of final and binding nature has been tested in the Constitutional Court in PUU case No. 32/PUU-XIX/2021 jo. No. 31/PUU-XI/2013, and then authorized the State Administrative Court to be able to test DKPP decisions. Thus, corrections to DKPP's ethical decisions can already be tested through the means of enforcing state administrative law (administrative law) with PTUN (beschikking) which is expanded so that it requires adjustments to the norms of the State Administrative Court Procedure Law.